A case of spastic paraplegia-15 with a novel pathogenic variant in ZFYVE26 gene. (2nd December 2019) - Özdemir, Taha Reşid; Gençpınar, Pınar; Arıcan, Pınar; Öztekin, Özgür; Dündar, Nihal Olgaç; Özyılmaz, Berk
Abstract: Hereditary spastic paraplegia (HSP) is a group of rare neurodegenerative disorder with genetic and clinical heterogeneity. It has autosomal dominant (AD), autosomal recessive (AR) and X-linked forms. HSPs are clinically classified into 'pure' and 'complicated' (complex) forms. SPG11 ( KIAA1840 ) and SPG15 ( ZFYVE26 ) are the most common ARHSPs with thin corpus callosum (TCC). They typically present with early cognitive impairment in childhood followed by gait impairment and spasticity in the second and third decades of life. Here, we present a patient girl, born to a couple who were first cousins, was admitted to the pediatric neurology outpatient clinic at 14 years of age because of walking with help, dysarthria and forgetfulness. Her examination revealed a motor mental retardation, bilateral leg spasticity, increased deep tendon reflexes in lower limbs, bilateral pigmentary retinopathy; TCC and white matter hyperintensities on brain MRI, sensorimotor axonal polyneuropathy findings in lower limbs on electromyography. Based on the clinical features and the imaging studies, the diagnosis of HSP was suspected. Targeted next generation sequencing (NGS) was performed using Inherited NGS Panel that consists of 579 gene associated with Mendelian disorders. Analysis of the patient revealed a c.6398_6401delGGGA(p.Arg2133Asnfs*15)(Exon35) homozygous novel change in ZFYVE26 gene. Genotype-phenotype correlation of HSP is complicated due to heterogeneity. The clinical similarity of HSP types increases the importance of genetic diagnosis. There are few reports about pathogenic variants in ZFYVE26 gene in the literature. This case report is one of the few studies that revealed a novel pathogenic variant in ZFYVE26 gene using NGS.